Betel leaf (Piper betle L.) essential oil microemulsion: Characterization and antifungal activity on growth, and apparent lag time of Aspergillus flavus in tomato paste. (January 2017) - Basak, Suradeep; Guha, Proshanta
Abstract: The present study aimed at characterization of betel leaf ( Piper betle L.) essential oil based microemulsion (BLEO-ME) and modelling its effect on growth of Aspergillus flavus in tomato paste. The microemulsion was formulated using betel leaf essential oil, Tween 20 and water by low energy emulsification method. The average droplet size of formulated emulsions having different concentration of surfactant (5%, 10% and 15%) and BLEO (2.5%, 5% and 10%) was evaluated. The formulated BLEO-ME was observed to be kinetically and thermodynamically stable for at least 90 days at 4 °C. Primary modelling estimated maximum growth rate ( μ max ) and apparent lag time ( λ ) of the selected mould in tomato paste. Secondary modelling was performed to evaluate the effect of different concentration of BLEO on estimated growth parameters. Estimated E max (minimum concentration of oil at which mould growth was inhibited) and MIC (minimum inhibitory concentration of BLEO at which lag time is infinite) value against A. flavus was estimated to be 2.01 ppm and 3.55 ppm in tomato paste, respectively. Accuracy and bias factor of the fitted secondary models suggested good similarity between observed and estimated values of μ max and λ . The formulated BLEO-ME exhibited antifungal efficacy in tomato paste, which suggests its potential as natural preservative. Highlights: Formulation and characterization of betel leaf essential oil based microemulsion. Low-energy emulsification technique is cheap and industrial friendly. The effect of BLEO on maximum growth rate and apparent lag time was modelled. Antifungal efficacy of BLEO-ME in tomato paste suggests its applicability in food. BLEO is a promising food preservative to inhibit food spoilage.